2013
DOI: 10.1038/mt.2013.87
|View full text |Cite|
|
Sign up to set email alerts
|

Topical Application of Recombinant Type VII Collagen Incorporates Into the Dermal–Epidermal Junction and Promotes Wound Closure

Abstract: Patients with recessive dystrophic epidermolysis bullosa (RDEB) have incurable skin fragility, blistering, and skin wounds due to mutations in the gene that codes for type VII collagen (C7) that mediates dermal-epidermal adherence in human skin. In this study, we evaluated if topically applied human recombinant C7 (rC7) could restore C7 at the dermal-epidermal junction (DEJ) and enhance wound healing. We found that rC7 applied topically onto murine skin wounds stably incorporated into the newly formed DEJ of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 44 publications
3
39
0
7
Order By: Relevance
“…While it is possible that the gentamicin-treated sites had lower bacterial counts, the generation of new type VII collagen and AFs at the DEJ only in the gentamicintreated sites strongly suggests that the likely major mechanism by which gentamicin improved clinical wound healing was by its ability to read through PTCs and generate new type VII collagen and AFs. This is consistent with our previous study showing that topical recombinant type VII collagen promotes wound closure (8).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…While it is possible that the gentamicin-treated sites had lower bacterial counts, the generation of new type VII collagen and AFs at the DEJ only in the gentamicintreated sites strongly suggests that the likely major mechanism by which gentamicin improved clinical wound healing was by its ability to read through PTCs and generate new type VII collagen and AFs. This is consistent with our previous study showing that topical recombinant type VII collagen promotes wound closure (8).…”
Section: Discussionsupporting
confidence: 82%
“…These have included intradermal injection of allogeneic dermal fibroblasts or gene-corrected RDEB fibroblasts (11,14,16), intradermal injection of lentiviral vectors expressing type VII collagen (48), intradermal injection or topical application of recombinant type VII collagen protein (6)(7)(8), intravenous injection of type VII collagen protein itself or fibroblasts that synthesize and secrete type VII collagen (9,10,12), transplantation of bone marrow stem cells, and gene-corrected keratinocyte autografts (13,15,17,49). None of the above are consistently efficacious, and some of them involve substantial risk and considerable invasiveness.…”
Section: Patients and Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical studies 72 have shown that recombinant human C7 delivered by intradermal injection is capable of migrating to the basement membrane and being incorporated into the DEJ of Col7a1 null mice, causing an improvement in the blistering phenotype for up to 2 months. Topical application of human recombinant C7 (rC7) accelerated wound healing 73 in mice, and intravenously administered rC7 homed to engrafted RDEB mouse skin and restored C7, anchoring fibrils, and epidermal-dermal adherence. 72,74 Further animal studies in inbred golden retriever dogs with mild RDEB revealed that intravenous administration of rC7 results in reduced wound erythema and blistering.…”
Section: Protein Therapymentioning
confidence: 99%